High-energy X-ray applications: current status and new opportunities. (30th January 2018) - Šišak Jung, Dubravka; Donath, Tilman; Magdysyuk, Oxana; Bednarcik, Jozef
Abstract : Characterization of semi and noncrystalline materials, monitoring structural phase transitions in situ, and obtaining structural information together with spatial distribution of the investigated material are only a few applications that hugely benefitted from the combination of high-energy X-rays and modern algorithms for data processing. This work examines the possibility of advancing these applications by shortening the data acquisition and improving the data quality by using the new high-energy PILATUS3 CdTe detector.